Prevalence, diagnostic evaluation, and disease associations of blood-borne pathogens and ticks from domestic dogs and cats across Namibia - Oosthuizen, Marinda C. (University of Pretoria, 2025)
Thesis (PhD (Veterinary Tropical Diseases))--Univeristy of Pretoria, 2025.